The effect of radiation exposure on carbon fiber-reinforced Rohacell® core laminate structural composites. (July 2020) - Zaldivar, Rafael J; Marques, D; Barrie, C; Patel, D
Two equivalent density foams with identical shear strengths were used to manufacture carbon-fiber reinforced composite sandwich structures. One foam core system (Rohacell® 71 WF) has a cell diameter of 1117 µm and a wall thickness of 29 µm, while the second one (Rohacell® 71 HERO) has cell diameter of 146 µm and a wall thickness of 3 µm. A 60 Co source was used to expose composites from 0 to 12 Mrads of radiation. Tests were used to evaluate the effect of radiation on the core shear strength and failure mechanism for both types of composites. The WF composites experienced a 75% decrease in core shear strength, while the HERO only exhibited an 8% decrease. The fracture behavior of the WF composites changed from a more compliant to a brittle fracture path with increased radiation. The fracture modes for the HERO were similar and did not change characteristics, even with maximum radiation dosage. Thermal analysis also showed that even after composite thermal processing, the WF foam retained a lower Tg in comparison to the HERO foam. Dynamic mechanical analyzer also indicated a faster rate of Tg degradation for the WF foam composites as a function of radiation, suggesting a lower degree of crosslinking which resulted in fragmentation of the network. Thermal gravimetric analysis and size exclusion chromatography also exhibited an earlier onset of thermal degradation for the WF foams with radiation. This investigation suggests that changes in composite mechanical properties with radiation are related to both foam macrostructure and the degree of crosslinking of the polymer foam. Careful evaluation must be performed to establish proper selection of the composite core material based on end of life environmental exposure.